Assessment of Lipid Lowering Effects of Vitamin E (Medical Forum Monthly, 2024)
Objective: Aim of this study was to determine the role of antioxidant vitamin E in lowering the serum cholesterol and triglyceride levels. Place and Duration: This study was conducted in the department of Pharmacology, Faculty of Pharmacy, University of Karachi, Karachi. Duration of study was 42 days from1-03-2008 to 11-4-2008. Materials and Methods: Male 20 rabbits were equally divided into 2 groups, group A was served as control and the group B was vitamin E treated. All the animals were maintained on cholesterol rich diet for a period of 30 days in order to induce hypercholesterolemia. After induction of hypercholesterolemia the group B was given vitamin E in a dose of 8.57mg/kg/day while the control group A was maintained on distilled water only for a period of 42 days. At the end of 42 days the blood samples were collected from marginal ear vein of rabbits and were analyzed to determine the levels of cholesterol and triglycerides. Results: The results showed that there was decrease in the level of cholesterol but the level of triglyceride was reduced much significantly by administration of vitamin E. It has been reported earlier that vitamin E has potential to decrease levels of cholesterol and triglycerides. Conclusion: It can be concluded that vitamin E use can reduce the level of cholesterol and triglyceride in hypercholesterolemia and may prove to be beneficial.